2022
DOI: 10.3390/jcm11030482
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in Acute Ischemic Stroke Patients with Proximal Occlusions within the Anterior Circulation after Endovascular Therapy or Systemic Thrombolysis

Abstract: While endovascular treatment (ET) improves clinical outcomes in patients with proximal vessel occlusions compared to thrombolysis (IVT), the impact of ET on the frequency of stroke-associated pneumonia (SAP) is uncertain. We compared the rates of SAP in patients with large vessel occlusions in the anterior circulation after IVT or ET. We also determined risk factors for SAP, as well as the impact of SAP on early clinical outcomes. A total of 544 patients were treated with IVT, and 1061 patients received ET (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Second, stroke and the procedure of EVT may produce a considerable inflammatory response with both peripheral and central production of proinflammatory cytokines, chemokines, and cell adhesion molecules, thus affecting patient prognosis. [30][31][32] In addition, our study found a significant difference in age between the two groups, which was consistent with the findings of Muhl et al 23 Previous studies have revealed that elderly patients who receive EVT have worse functional outcomes than younger patients. 33,34 Notably, in our study, 120 patients were aged over 80, with 78 of them experiencing post-EVT infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, stroke and the procedure of EVT may produce a considerable inflammatory response with both peripheral and central production of proinflammatory cytokines, chemokines, and cell adhesion molecules, thus affecting patient prognosis. [30][31][32] In addition, our study found a significant difference in age between the two groups, which was consistent with the findings of Muhl et al 23 Previous studies have revealed that elderly patients who receive EVT have worse functional outcomes than younger patients. 33,34 Notably, in our study, 120 patients were aged over 80, with 78 of them experiencing post-EVT infection.…”
Section: Discussionsupporting
confidence: 92%
“…Infection has already been considered a determinant of outcomes after stroke; however, existing studies have mainly focused on the relationship between stroke-associated infection and clinical outcome in patients with AIS. 7,8,23,24 In our study, we compared and summarized the baseline characteristics, risk factors, and clinical outcomes of AIS patients with or without post-EVT infection.…”
Section: Discussionmentioning
confidence: 99%
“…MT is more invasive than iVT and requires sedation or mechanical ventilation, which may increase the risk of SAP. To answer this question, Muhl et al used data from a large prospective German stroke registry comparing patients undergoing reperfusion treatments for emergent large vessel occlusion of the anterior circulation [ 9 ]. Across the board, one out of five patients developed PAS and, as expected, SAP was associated with increased mortality and poor functional outcome; however, the rates of SAP between MT and iVT populations were not different.…”
mentioning
confidence: 99%